2017
DOI: 10.1002/ecy.2087
|View full text |Cite
|
Sign up to set email alerts
|

Hemiparasites can transmit indirect effects from their host plants to herbivores

Abstract: Parasitic plants can serve as critical intermediaries between their hosts and other organisms; however these relationships are not well understood. To investigate the relative importance of plant traits in such interactions, we studied the role of the root hemiparasite, Castilleja levisecta (Orobanchaceae), as a mediator of interactions between the host plants it parasitizes and the lepidopteran herbivore Euphydryas editha (Nymphalidae), whose caterpillars feed on Castilleja and sequester iridoid glycosides fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
1
5
1
Order By: Relevance
“…In previous work we found that greenhouse-grown C. levisecta produced largely aucubin, and E. editha larvae that ate it contained both aucubin and catalpol 52 ; this contrasts with our findings here. These differences in plant chemistry are likely because plants in the previous study were grown in the greenhouse, whereas plants used in the present study were field collected.…”
Section: Causes and Consequences Of Adopting A Novel Host The Ease With Which Checkerspots Adoptcontrasting
confidence: 99%
See 1 more Smart Citation
“…In previous work we found that greenhouse-grown C. levisecta produced largely aucubin, and E. editha larvae that ate it contained both aucubin and catalpol 52 ; this contrasts with our findings here. These differences in plant chemistry are likely because plants in the previous study were grown in the greenhouse, whereas plants used in the present study were field collected.…”
Section: Causes and Consequences Of Adopting A Novel Host The Ease With Which Checkerspots Adoptcontrasting
confidence: 99%
“…Iridoid glycoside uptake. In general, overall IG concentrations in larvae were similar to those in previous studies of related taxa at similar ontogenetic stages 41,51,52 . Concentrations were highest when larvae ate Plantago or C. hispida leaves and lower if they ate C. hispida bracts or either tissue type of C. levisecta.…”
Section: Causes and Consequences Of Adopting A Novel Host The Ease With Which Checkerspots Adoptsupporting
confidence: 86%
“…The potential impacts of hemiparasites on communities aligns with a growing body of literature demonstrating that organisms with a parasitic lifestyle act as facilitators to alter patterns of co‐occurrence and trophic complexity (Hatcher et al, 2012 ). For example, because many parasites can serve as both predators and prey, they play an outsized role in food webs relative to their biomass (Haan et al, 2018 ; Lafferty et al, 2006 ). Parasites can also influence the outcome of trophic interactions at a community scale (Hudson et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…In ecological communities, species are linked to each other in networks of direct and indirect interactions (Hartley et al 2015, Haan et al 2018. As a consequence, changes in the presence of some species may have cascading effects at other trophic levels that can indirectly affect ecological processes.…”
Section: Introductionmentioning
confidence: 99%